An Empirical Study to Determine the Perceptual Positioning of ten well Known Toothpaste Brands - Ganguly, A.P. (Indian Journal of Marketing, 2005)
Positioning is not what you do to a product. Positioning is what you do to the mind of the prospect (Ries and Trout, 1986).The purpose of positioning is to create a distinct position or place for a particular brand in the minds of the target market so that it stands apart from competing brands. The objectives of this paper are: 1. To know by means of perceptual maps, ’how’ target customers (youth segment for this research paper) perceive one brand vis-Ã -vis other brands. 2. To understand how brands are positioned in relation to relevant attributes 3. To find ’gaps’ or ’holes’ for potential opportunities of launching a new product. 4. To check whether marketing communications have been successful in placing the brand in the desired position.